Caracterização química e atividade inseticida de óleos essenciais cítricos sobre dysmicoccus brevipes (cockerell, 1893) (hemiptera:pseudococcidae) - Martins, Gisele dos Santos Oliveira (2016)
Cochineal-white, Dysmicoccus brevipes, (Hemiptera: Pseudococcidae) promotes serious phytosanitary problems in pineapple and coffee, among which, reduction in the quantity and quality of fruits and grains, respectively. Given the problems arising with the